Plasmid-mediated colistin resistance encoded by mcr-1 gene in Escherichia coli co-carrying blaCTX-M-15 and blaNDM-1 genes in pediatric patients in Qatar - Tsui, Clement K. M. (2020)
Plasmid-mediated colistin resistance encoded by mcr-1 gene in Escherichia coli co-carrying blaCTX-M-15 and blaNDM-1 genes in pediatric patients in Qatar